Development of poorly differentiated invasive squamous cell carcinoma in giant Bowen's disease: a case report with dermatoscopy - Bengu Nisa Akay; Aysenur Maden; Oguzhan Kocak; Seher Bostanci; Ayse Boyvat; Pelin Kocyigit; Aylin Okcu Heper (Mattioli1885, 2016)
Bowen's disease (BD) is an in situ form of squamous cell carcinoma (SCC), often occurring in the chronically UV-damaged skin of elderly people. The risk of progression of BD to invasive SCC varies between 3% and 5%, and one-third of invasive tumors may metastasize. Herein we discuss the dermatoscopic findings of a case of giant Bowen's disease, which progressed to poorly differentiated invasive SCC.